2020
DOI: 10.3892/ijmm.2020.4526
|View full text |Cite
|
Sign up to set email alerts
|

A novel microRNA signature for pathological grading in�lung adenocarcinoma based on TCGA and GEO data

Abstract: Lung adenocarcinoma (LUAd) is one of the most common types of lung cancer and its poor prognosis largely depends on the tumor pathological stage. critical roles of microRNAs (miRNAs) have been reported in the tumorigenesis and progression of lung cancer. However, whether the differential expression pattern of miRNAs could be used to distinguish early-stage (stage I) from mid-late-stage (stages II-IV) LUAd tumors is still unclear. In this study, clinical information and miRNA expression profiles of patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Considering that the abnormal expression of miRNA can affect the molecular functions and biological processes of a variety of tumors, many attempts have been made to use miRNA as a biomarker to accurately predict the diagnosis and prognosis of cancers. [20][21][22][23] Up to now, several studies have also focused on the discovery of miRNAs as biomarkers for nasopharyngeal cancer diagnosis. Huo Zhang et al identified a 7-miRNA signature in plasma for nasopharyngeal cancer detection.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the abnormal expression of miRNA can affect the molecular functions and biological processes of a variety of tumors, many attempts have been made to use miRNA as a biomarker to accurately predict the diagnosis and prognosis of cancers. [20][21][22][23] Up to now, several studies have also focused on the discovery of miRNAs as biomarkers for nasopharyngeal cancer diagnosis. Huo Zhang et al identified a 7-miRNA signature in plasma for nasopharyngeal cancer detection.…”
Section: Discussionmentioning
confidence: 99%
“…Predicting NSCLC subtypes by identifying specific genotypes is a potentially powerful method that can be recommended as a special marker for IHC-stained slides. Therefore, several references determined the sensitivity and specificity of genetic markers to discriminate the subtypes of NSCLCs, as shown in Table 2 (31)(32)(33)(34)(35)(36)(37). A retrospective study selected the genetic features from 77 ADCs and 73 SCCs to construct the support vector machine (SVM) and random forest (RF) classifier (32).…”
Section: Diagnosing Histologic Subtypes Of Nsclcs Based On Digital Histopathologic Slides and Gene Profilesmentioning
confidence: 99%
“…Gene expression variants have been reported to have critical roles in tumor progression and metastasis, thus suggesting the feasibility of genetic biomarkers for the detection and classification of NSCLC subsets (37). Although the gene profiles have been identified as predictors of clinical diagnosis or NSCLC outcomes, whether gene profiles can be used as pathologic staging marker has not been established.…”
Section: Predicting Pathologic Stages Of Nsclcs Based On Gene Profilesmentioning
confidence: 99%
“…With the application of gene sequencing in tumours, miRNAs can be considered as new biomarkers in patient prognosis prediction and drug resistance (11)(12)(13). In addition, integration of multiple miRNAs may be more efficient than a single miRNA for prognosis prediction (14,15). A large number of studies have identified a series of miRNA signatures that can serve as potential biomarkers for LUAD patient prognosis prediction (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, integration of multiple miRNAs may be more efficient than a single miRNA for prognosis prediction (14,15). A large number of studies have identified a series of miRNA signatures that can serve as potential biomarkers for LUAD patient prognosis prediction (15,16). It is well known that miRNAs have important roles in the regulation of gene expression, either through a single miRNA that regulates the expression of multiple genes or through the combination of several miRNAs that finely regulate the expression of a gene, which in turn regulates various physiological processes, cellular functions, and signalling pathways (17,18).…”
Section: Introductionmentioning
confidence: 99%